IJCM_170A: Exploring 10-year cardiovascular risk assessment through the utilization of the Framingham Risk Score(FRS): A Cross-Sectional Study - Saini Mohit; Bano Tanveer; Jain Seema; Singh Ganesh; Kumar Sanjeev; Gautam Neelam (Wolters Kluwer Medknow Publications, 2024)
Background: Cardiovascular diseases (CVDs) are a major global health concern, causing significant morbidity and mortality. A joint report by the Harvard School of Public Health and World Economic Forum highlights a substantial economic burden of $47 trillion due to CVD from 2010-2030. Predictions suggest 23.6 million deaths from CVD by 2030. Identifying individuals at CVD risk is crucial for prevention. The Framingham Risk Score (FRS) is a key tool for estimating 10-year CVD risk. Objective: To estimate the ten-year risk of developing cardiovascular disease using Framingham heart risk assessment score. Methodology: In the period from January to July 2023, a cross-sectional study spanning six months was conducted at the Community Medicine OPD of LLRM Medical College, Meerut. Adult residents were interviewed, and data, comprising anthropometric measurements and blood investigations (fasting blood sugar and lipid profile), were gathered using a pretested semi-structured questionnaire. The Framingham Risk Score, a gender-specific algorithm, was employed to assess the 10-year cardiovascular risk for each individual. Results: Among 298 participants, 13.3% had an intermediate risk, and 4.2% had a high risk of cardiovascular disease in the next 10 years. Higher prevalence of intermediate and high risk was observed in males. Urban adults exhibited prevalent cardiovascular risk factors, projecting a 2.8% high-risk prediction. Conclusion: In this study, males exhibited a higher prevalence of intermediate and high risk than females. The projected high-risk prediction for CVD in the next 10 years among participants was 2.8%.